1999
DOI: 10.1093/intimm/11.8.1327
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral human CD8+CD28+T lymphocytes give rise to CD28–progeny, but IL-4 prevents loss of CD28 expression

Abstract: At birth, virtually all peripheral CD8(+) T cells express the CD28 co-stimulatory molecule, but healthy human adults accumulate CD28(-)CD8(+) T cells that often express the CD57 marker. While these CD28(-) subpopulations are known to exert effector-type functions, the generation, maintenance and regulation of CD28(-) (CD57(+) or CD57(-)) subpopulations remain unresolved. Here, we compared the differentiation of CD8(+)CD28(bright)CD57(-) T cells purified from healthy adults or neonates and propagated in IL-2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…The CD28 molecule is lost by normal lymphocytes after repeated stimulation with IL-2 in long-term culture (Labalette et al, 1999). Based on the fact that T lymphocytes from B-CLL patients have a phenotype of activated cells, that is, Dianzani et al, 1994;Van den Hove et al, 1998;Scrivener et al, 2001), it can be suggested that the loss of CD28 molecule on T lymphocytes before culture is related to a prolonged in vivo activation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CD28 molecule is lost by normal lymphocytes after repeated stimulation with IL-2 in long-term culture (Labalette et al, 1999). Based on the fact that T lymphocytes from B-CLL patients have a phenotype of activated cells, that is, Dianzani et al, 1994;Van den Hove et al, 1998;Scrivener et al, 2001), it can be suggested that the loss of CD28 molecule on T lymphocytes before culture is related to a prolonged in vivo activation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic, phytohaemagglutinin or anti-CD3 stimulation of CD8+ CD28+ T cells gives rise to a CD8+ CD28¡ T cell population [71]; this was accelerated by the presence of type I IFN [99]. Loss of CD28 has also been demonstrated for cord blood cells cultured in IL-12 and IL-15 [100], naïve cells maintained in IL-15 (reversed by IL-21) [101] and CD8+ CD28+ cells propagated using soluble anti-CD3 antibody and IL-2 (reversed by IL-4) [102]. Taken together these studies provide a strong indication that CD8+ CD45RA+ CD28¡ T cells develop in conditions of antigen absence in a particular cytokine environment, although it is unclear why this occurs to a greater extent during HCMV infection compared to other chronic viral infections.…”
Section: What Is the Lineage Relationship Of Cd45ra+ Cd28¡ (Revertantmentioning
confidence: 95%
“…The lack of a difference in some experiments appeared to be related to the time point analyzed, with day 7 showing a difference in all experiments, day 8 in most, and day 9 in none, even in the same donor. In most donors, effector T cells maintained the expression of CD28 for the 7-8 days of culture, but by 9 days higher numbers of CD28 Ϫ T cells were observed in some donors, perhaps due to the accumulation of cytokines that are known to modulate the expression of CD28 (30)(31)(32). These data suggest that 4-1BBL can be more effective than B7.1 in driving human memory T cells into mature CD27 Ϫ effector cells, at least under some conditions.…”
Section: -1bbl and B71 Costimulation And The Efficacy Of Effector Tmentioning
confidence: 99%